Evaluación técnico-financiera para el diseño de una línea de transferencia de fluidos producidos desde la estación Toro sentado al cluster bengala en el bloque Caracara (2017)
In this project the technical-financial evaluation for the design is made a transfer line of the Sitting Station Toro to the Bengal Cluster, in order to take advantage of the existing transfer lines between the Bengal Cluster and the Jaguar Station, guaranteeing a transport of fluids Continuous, with lower risks associated with field operations, and resulting in greater profitability to the company compared to the existing system of production of car tank tanks used.